Kepemimpinan Kepala Madrasah dalam meningkatkan Budaya Organisasi Produktif di Madrasah Tsanawiyah Swasta Nurul Islam Desa Kembang Tanjung Kecamatan Mersam Kabupaten Batang Hari. - Naziha Amani; Sukatin Sukatin; Amrizal Amrizal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The leadership of the Head of Madrasah refers to the leader's ability to motivate and influence people to be willing to take actions aimed at achieving goals through the courage to make decisions about the activities that need to be undertaken. A productive organizational culture is a way to achieve better results for the organization, groups, and individuals by understanding and managing performance in accordance with planned targets, standards, and specified competency requirements. This research is descriptive qualitative. The results of this study show that the leadership of the Head of Madrasah enhances the Culture of Productive Organizations, it has been well implemented, including activities such as preparing to develop the organizational structure through the vision and goals of the madrasah, defining the roles of teachers in the organizational structure and providing intellectual stimulation, and carrying out the leadership of the Head of Madrasah with innovation by offering individual support and examples of organizational values through activities aimed at improving communication with educators and educational staff regarding the achievements to be attained, always providing motivation for task execution, especially in the implementation of the madrasah's organizational culture, and conducting supervision to encourage participation in decision-making.